The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1109/tgrs.2014.2360989
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Evaluation of SAR-GMTI Missions for Maritime Applications

Abstract: Abstract-This paper proposes a new optimized multichannel synthetic aperture radar (SAR) configuration, based on receiving antennas with non-uniformly displaced phase centers, intended for ground moving target indication (GMTI) applications over maritime scenarios. This system is compared with current SAR missions, such as TerraSAR-X (TSX) or TanDEM-X (TDX). The GMTI capabilities of the different configurations are analyzed in a two-level performance approach. First, an intensive numerical simulation evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
(65 reference statements)
2
25
0
Order By: Relevance
“…With the available raw data, we can easily focus the moving target by using the relationship (8). Hence, the raw data is first transformed to the frequency domain by a 2-D Fourier transform.…”
Section: B Focusing With the Original Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…With the available raw data, we can easily focus the moving target by using the relationship (8). Hence, the raw data is first transformed to the frequency domain by a 2-D Fourier transform.…”
Section: B Focusing With the Original Approachmentioning
confidence: 99%
“…The wave number k x is now defined by where γ = 0.9553 in this case. The change of variable from ω to k ρ relies on the relationship (8). The data after the interpolation is scaled with the factor and multiplied with the exponential term given in (10).…”
Section: B Focusing With the Original Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In coastal areas, even for a maritime surveillance system, the classical SAR and GMTI modes are very useful for imaging the infrastructures along the coastlines and within harbors. Moreover, the applicability of SAR-GMTI techniques to maritime scenarios was recently demonstrated in [14]. The SmartRadar pod system has several advantages with regard to implementing such different radar mode types, especially due to its active electronically scanned array (AESA) antenna, the wide overall bandwidth, several receive channels, and a very flexible and configurable core electronics (refer to Table I and to [8] for technical details).…”
Section: Modes For Various Applicationsmentioning
confidence: 99%
“…The operation of spaceborne SAR-GMTI has been widely evaluated for road traffic monitoring [8]- [10]; and a lot of effort has been devoted to the analysis and definition of new processing strategies and algorithms [11]- [14]. Nevertheless, multichannel SAR-GMTI is not yet being extensively employed in the maritime surveillance field for vessel detection; but some preliminary studies have shown its potential capability [15]- [19].…”
mentioning
confidence: 99%